Listening in the Mix: Lead Vocals Robustly Attract Auditory Attention in Popular Music - Bürgel, Michel; Picinali, Lorenzo; Siedenburg, Kai (Frontiers in Psychology, 2021)
Listeners can attend to and track instruments or singing voices in complex musical mixtures, even though the acoustical energy of sounds from individual instruments may overlap in time and frequency. In popular music, lead vocals are often accompanied by sound mixtures from a variety of instruments such as drums, bass, keyboards, and guitars. However, little is known about how the perceptual organization of such musical scenes is affected by selective attention, and which acoustic features play the most important role. To investigate these questions, we explored the role of auditory attention in a realistic musical scenario. We conducted three online experiments in which participants detected single cued instruments or voices in multi-track musical mixtures. Stimuli consisted of two-second multi-track excerpts of popular music. In one condition, the target cue preceded the mixture, allowing listeners to selectively attend to the target. In another condition, the target was presented after the mixture, requiring a more “global” mode of listening. Performance differences between these two conditions were interpreted as effects of selective attention. In Experiment 1, results showed that detection performance was generally dependent on the target’s instrument category, but listeners were more accurate when the target was presented prior to the mixture rather than the opposite. Lead vocals appeared to be nearly unaffected by this change in presentation order and achieved the highest accuracy compared with the other instruments, which suggested a particular salience of vocal signals. In Experiment 2, filtering was used to avoid potential spectral masking of target sounds. Although detection accuracy increased for all instruments, a similar pattern of results was observed regarding the instrument-specific differences between presentation orders. In Experiment 3, adjusting the sound level differences between the target instruments reduced the effect of presentation order, but did not affect the differences between instruments. While both acoustic manipulations facilitated the detection of target instruments, vocal signals remained particularly salient, which suggests that the manipulated features did not contribute to vocal salience. These findings demonstrate that lead vocals serve as robust attractor points of auditory attention regardless of the manipulation of low-level acoustical cues.